Does standoff material affect acoustic radiation force impulse elastography? A preclinical study of a modified elastography phantom - Katharina Hollerieth; Bernhard Gaßmann; Stefan Wagenpfeil; Stephan Kemmner; Uwe Heemann; Konrad Friedrich Stock (Ultrasonography, 2018)
Purpose This study was conducted to determine the influence of standoff material on acoustic radiation force impulse (ARFI) measurements in an elasticity phantom by using two different probes. Methods Using ARFI elastography, 10 observers measured the shear wave velocity (SWV, m/sec) in different lesions of an elasticity phantom with a convex 4C1 probe and a linear 9L4 probe. The experimental setup was expanded by the use of an interposed piece of porcine muscle as standoff material. The probe pressure on the phantom was registered. Results Faulty ARFI measurements occurred more often when quantifying the hardest lesion (74.0 kPa 4.97 m/sec) by the 9L4 probe with the porcine muscle as a standoff material interposed between the probe and the phantom. The success rate for ARFI measurements in these series was 52.4%, compared with 99.5% in the other series. The SWV values measured with the 9L4 probe were significantly higher (3.33±1.39 m/sec vs. 2.60±0.74 m/sec, P<0.001 in the group without muscle) and were closer to the reference value than those measured with the 4C1 probe (0.25±0.23 m/sec vs. 0.85±1.21 m/sec, P<0.001 in the same group). The SWV values measured when using the muscle as a standoff material were lower than those without the muscle (significant for 9L4, P=0.040). The deviation from the reference value and the variance increased significantly with the 9L4 probe if the muscle was in situ (B=0.27, P=0.004 and B=0.32, P<0.001). In our study, the pressure exerted by the operator had no effect on the SWV values. Conclusion The presence of porcine muscle acting as a standoff material influenced the occurrence of failed measurements as well as the variance and the accuracy of the measured values. The linear high-frequency probe was particularly affected.